Index of rural development: a systematic literature review - Palacio, Vinicius [UNESP]; Lourenzani, Wagner Luiz [UNESP]; Bernardo, Cristiane Hengler Correa [UNESP] (Univ Cruz Alta, 2018)
This article aims to analyzing the state of the art on the index of rural development, by the denominated Systematic Literature Review (SLR). In order to reach this objective, the model proposed by Conforto, Amaral e Silva (2011) was used, establishing a series of systematic procedures for the collection, processing and analysis of scientific works. Twenty-seven national and international works were selected, cataloged and analyzed. Although increasing in the period between 2004 and 2017, it is understood that there is room for the development of new studies that address this issue, fostering new knowledge and subsidizing decision makers. It is concluded that this work contributed methodologically to the study area, through the use of RBS, as well as to the scientific debate on the theme of rural development, especially when adopting a quantitative approach.
Keywords: Rural Development; SLR; Development Index